PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOOK BERBASIS KEARIFAN LOKAL PADA PEMBELAJARAN TEMATIK TEMA 5 PENGALAMANKU SUB BAB PENGALAMANKU DI TEMPAT WISATA - Winda Anggriyani Uno; Irmayani Halim; Syahriyanto Syahriyanto (PENDIDIKAN SAINS DAN TEKNOLOGI, 2021)
This research aims to develop teaching media product in the form of pop up book media based on local wisdom. In the fifth grade student thematic learning at SDN 12 Tilamuta which is valid and practical to use in the learning process. The research method is R&D (Research and development), with the ADDIE development model used in analysis, design, development, implementation and evaluation. Based on the results of the assessment analysis obtained from language, media and material validation experts, they obtained an average score that met the valid criteria. Then the results of the practical analysis of students and teachers obtained an average score that met the very practical criteria. So, it can be concluded that the pop up book media based on local wisdom in thematic learning is valid and practical to use in the learning process.